PSYCHO-PHYSIOLOGICAL CHARACTERISTICS OF ADOLESCENTS WITH HIGH RISK OF DEVELOPMENT OF BEER DEPENDENCE - A.G. Solov'ev; G.A. Novikova ("Paediatrician" Publishers LLC, 2009)
The aim of present trial is study of psycho physiological peculiarities of adolescents with high risk of development of beer dependence. 143 schoolchildren from 5-11 form of Archangelsk schools of general education took part in trial. 3 groups of adolescents were formed, depending of summarized indices of beer alcoholization: group of high grade of alcoholization (35.5%), medium grade (45.2%) and low grade (19.3%). Adolescents with high risk of development of beer dependence are characterized with lowering of simple visual-motor and audio-motor response rate, complex visual-motor response rate, complex sensomotor response rate on moving object, decrease of stability of sensomotor processes and attention stability, stability of mental work and mental efficiency depending on time, efficiency in deficit of time and information. These disorders may be used in early diagnostics of beer dependence in structure of primary and secondary psycho prophylactic measures. Key words: adolescents, beer dependence, psycho physiological peculiarities, prophylaxis. (Voprosy sovremennoi pediatrii - Current Pediatrics. 2009;8(1):25-29)